Coordinated regulation of hepcidin and iron importers through iron excess and erythropoietin signals in enterocyte and hepatocytes in mice models - Giorgi, Gisela (2017)
The erythropoietic activity is the main inhibitor of the hepcidin expression, the key regulator of the iron metabolism that reduces the intestinal absorption of iron and the release from macrophages. Objective: To evaluate the response of functional axis “HEPCIDIN- DMT1-ZIP14 using mice models of iron-overload and also an erythropoiesis induced by EPO. Materials and Methods: CF1 mice (25±5g) were divided into 4 groups (n=4/group;block design): 1)Iron-overload and erythropoietin(IO+EPO) Fe-Saccharate ip (days 0,4,8,12;1800mg/kg) and EPO ip(days 17,18,19;20000UI/ kg);2)Iron-overload(IO);3)Erythropoietin(EPO);4)control (C).The Protocol was approved by the Committee on Experimental Animal Use and Care-UNS. Immunohistochemistry: DMT1, ZRTIre like protein14 (ZIP14),prohepcidin,ferritin. Results: Duodenum: In control and EPO, ZIP14 was found in enterocytes apical membrane, while a slight basolateral expression was seen in iron-overload with and without EPO. DMT1 in enterocyte cytoplasm was moderated in Control, while in Iron-overload it was slight. In EPO and IO+EPO, the apical DMT1 was intense. Liver: The prohepcidin expression was slight in EPO, moderated in control and intense in IO and IO+ EPO. Both ZIP14 and ferritin in hepatocyte cytoplasm were weak in C and in EPO, they were intense in iron-overload and IO+EPO.Evident DMT1 expression was detected in the cell membrane and in cytoplasm of hepatocytes in EPO, while a weak expression was observed in C. In IO+EPO and IO, DMT1 expression was slight in hepatocytes cytoplasm. Conclusions: Two signals could induce speciﬁc response for each group: (i) iron-signal, induced prohepcidin synthesis, which reduced the duodenal iron uptake through DMT1 and ZIP14 and increased the hepatic iron storage through ZIP14, reducing iron availability; (ii) EPO-signal, which affected duodenal iron uptake by DMT1 and, therefore, allowed an iron supply to the bone marrow.